Development and validation of an instrument to access the lecturers’ performance in the education and teaching duties - Yusrizal,; A. Halim, (penerbit ukm, 2009)
In this study, an instrument was developed to access the lecturers’ performance in performing the education and teaching duties. The steps in the development of the instrument involves the development of conceptual and operational definition of the lecturers’ performance variable, the drafting of the lecturers’ performance indicators and items piloting the instrument with expert, and university students. The instrument was also piloted for second time with university students. Based on the operational definition and on the assessment conducted on the experts and students, it was obtained seven lecturers’ performance indicators and 71 items. The pilot test with experts and university students showed that the instrument has good construct validity. The calculation of reliability coefficient which was analyzed by using the alpha Cronbach formula showed the coefficient of 0.931 for the first pilot test and 0.934 for the second one.